Double your haircolor income in 30 days! - Foley, Mark D. (Thomson Delmar Learning, 2005)
Many professional hair designers do not realize their financial goals because they have not learned how to package themselves and their offerings for top earnings. This text solves those problems, ensuring that new and future professionals immediately get started on the track to success. The author has spent 10 years uncovering the secrets that top-earning salon professionals have kept to themselves. Here, the secrets to top financial success as a salon professional are revealed in an easy-to-read, step-by-step format. Students will regard this text as the most practical resource fueling their success